Indications for and histological diagnosis of liver biopsies at Helen Joseph Hospital - Muramira, M Nobert (My University, 2017)
Introduction: Liver pathology is an important contributor to the global burden of disease and is the eighth leading cause of death among South Africans.(1-3) Liver disease is particularly frequent in HIV-infected South Africans.(4, 5) The ongoing evolution of the HIV/AIDS epidemic of Southern Africa requires that the spectrum of liver disease in this region be well described and meticulously monitored.Objectives: The primary aim of this study was to describe the histological result of liver biopsies of patients attending the Helen Joseph Hospital (HJH). Methods: This was a cross-sectional, retrospective study. A review of medical records of adult patients admitted to the HJH, who had liver biopsies done from 1st January 2008 to 30th June, 2013 was performed. Results: 107 liver biopsies fulfilled the entry criteria of the study. Patients’ mean age was within ±13.5 years of 41.9 years of age. Two-thirds (65.4%) were HIV-infected. Of this group, 70% were severely immune compromised viz. CD4≤200 cells/mm3. Two-thirds (62.9%) of the HIV-infected were on ART. A definite and/or probable diagnosis was achieved in 72% of the entire cohort, where the single most frequent infectious pathogen was Mycobacterium tuberculosis (n=18/33, 54.5%).Of the group with confirmed TB of the liver, a pre-biopsy diagnosis of hepatic TB had been made in only nine patients (50%). Eighty percent of those diagnosed with drug-induced liver injury (DILI) were HIV-infected. Exposure to either or both TB and antiretroviral drugs was frequent. HIV-infected women were three times more likely to experience DILI than infected men. Liver biopsy confirmed the diagnosis of all patients categorised as having malignancy, alcoholic liver disease (ALD) and non-Alcoholic Fatty Liver Disease (NAFLD), p=0.000. In addition, a high level of certainty was achieved with regard to the categories of Infection and DILI, p=0.000. The causes of liver disease in the HIV-infected and the uninfected differed with regard to all the diagnostic categories studied. Specific and coherent antiviral management of those with hepatitis B and C infections was weak or non-existent. Conclusions: In the era of a changing HIV epidemic, liver biopsy continues to provide diagnostic value to the management of both the HIV-infected and uninfected.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Internal Medicine Johannesburg, 2017
Keywords: HIV-infected South Africans; Liver Diseases